Implementation of the Six Sigma-DMAIC Method for Quality Control in the Red Brick Production Process at Pondok Batu Bata Kampung 1 Tarakan - Hidayat, Nurul; Maulana, Ivan; Az-Zahra, Annazwa Zafira; Zain, Rofiqoh Nadiyah; Harpan, Regina Putri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Product quality is a key factor in the manufacturing industry, including in the production of red bricks carried out by Pondok Batu Bata Kampung 1 in Tarakan. This study uses the Six Sigma technique as a quality control strategy to improve the red brick manufacturing process, with the aim of increasing production efficiency and product quality. To find, evaluate, and minimize variations that cause product defects, the Six Sigma process is used. Define, Measure, Analyze, Improve, and Control are the steps of the DMAIC technique used. These findings indicate that Six Sigma can increase customer satisfaction while reducing the proportion of defective goods. With proper implementation, this method not only improves product quality but also provides a competitive advantage for Pondok Batu Bata Kampung 1 in the midst of market competition.